STAR-RIS assisted multi-user wireless system beamforming design in TS mode - LIU Gang; LI Mingtai; PAN Cheng; GUO Yi; FU Shaozhong (Dianxin kexue)
Simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) has the capability of simultaneous transmission and reflection, extending the communication capacity of conventional RIS (CRIS) from half-space to full-space. For the multi-user multiple-input single-output (MISO) communication system assisted by STAR-RIS, a beamforming algorithm based on time switch (TS) mode was proposed to minimize transmission power. Firstly, maximum ratio transmission (MRT) was used to get the initial BS transmitting beamforming. Secondly, TS slot orthogonality and channel gain maximum (CGM) were used to decouple the non-convex problem into the constant mode non-convex problem and the semi-definite programming (SDP) problem. Finally, manifold optimization and interior point method were used to jointly solve these problems. The simulation results show that, STAR-RIS can effectively reduce the transmission power compared with conventional RIS. Under the same SINR（signal-to-noise ratio）. The proposed algorithm has lower transmitting power than the mainstream algorithm. TS mode has lower transmitting power than energy splitting (ES) mode at low SINR.